Agresja wśród młodzieży gimnazjalnej w zielonogórskiej szkole = Aggression among Zielona Góra`s lower secondary school youth - Ajszpur, Małgorzata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the article the author discusses the circumstances which condition the phenomenon of youth aggression. The first part of the paper presents the theoretical issues related to the topic, e.g. definitions of aggression, its typology, theories of aggressive behaviour, factors behind aggression as well as issues related to preventing aggression.
Keywords: Zielona Góra; uczniowie gimnazjów; szkolnictwo; agresja